Integration of Artificial Intelligence Applications and Knowledge Management Processes for Construction Projects Management - Meervat R. Altaie; Marwa M. Dishar (Civil Engineering Journal, 2024)
Artificial intelligence systems have gained access to various scientific and research fields, especially in the construction industry. The study seeks to confirm the vital role of introducing Knowledge Management (KM) integrated with Artificial intelligence (AI) applications in the projects. It requires qualifying engineers and imposing their current qualifications to achieve the benefits of Integration of AI Applications based on KM processes to perform their professional roles and recognize the need to develop their capabilities through training and development. The field survey was intended only for 85 engineers working on construction projects (public and private sectors). Three axes were clarified to allocate the extent of the sample response and determine the benefits of using the KM process and AI applications for the success of construction projects. The results showed a positive relationship between the demographic variables of the response and the benefit of using the KM process and AI applications and explaining the variance in the regression relationships. Therefore, the study suggests integrating AI applications based on the KM process to achieve business goals and effectively benefit and exchange management, as its use leads to faster and more effective decision-making, especially if the project strategy approves it. Doi: 10.28991/CEJ-2024-010-03-06 Full Text: PDF